THE ROLE OF NIGERIAN INVESTMENT PROMOTION COMMISSION (NIPC) IN ATTRACTING FOREIGN DIRECT INVESTMENT IN NIGERIA - Zakari, Abubakar; Aliero, Haruna Muhammed; Abdul-Quadir, Ahmed Bawa (European Scientific Journal, ESJ, 2012)
This study examines the role of Nigerian Investment Promotion Commission (NIPC) in attracting Foreign Direct Investment (FDI) in Nigeria. Data for the study was collected from secondary sources to measure FDI inflow before the establishment of NIPC i.e. 1981-1995 and after the establishment of NIPC i.e. 1996-2010. Independent t Test was applied in analyzing the data. Findings from the result reveal that there is a significant correlation between the establishment of NIPC and an increase in FDI inflow. Secondly, the study finds that the average value of FDI inflows prior to the establishment of NIPC differed from the one after the establishment of NIPC. And lastly, the results revealed that NIPC had succeeded in influencing the growth of FDI in Nigeria. The study therefore recommends that government should pursue more credible and sound macroeconomic policies and provide conducive environment for the FDI to flourish.